2002
DOI: 10.2307/1554966
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among genera in Saniculoideae and selected Apioideae (Umbelliferae) inferred from nrITS sequences

Abstract: The internal transcribed spacers (ITS1 and ITS2) of 18S-26S nuclear ribosomal DNA were newly sequenced for eight species of Umbelliferae (six species from subfamily Saniculoideae: Actinolema macrolema, Astrantia minor, Eryngium giganteum, E. coeruleum, Hacquetia epipactis, and Lagoecia cuminoides, two species from subfamily Hydrocotyloideae: Dickinsia hydrocotyloides and Azorella trifurcata), as well as Hohenackeria exscapa, a species of uncertain position in the family. Phylogenetic analyses of new data, plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Sáenz (1981), Pujadas Salvà (2003, Baranski et al (2006), and Mezghani et al (2014) indicated that fruits provided critical taxonomic characters distinguishing taxa within Daucus since fruits tend to show less phenotypic plasticity in comparison with other plant organs. Other studies questioned the utility of fruit characters alone as a practical tool to classify taxa in the Apiales (Downie and KatzDownie 1999;Katz-Downie et al 1999;Spalik et al 2001;Vallejo-Roman et al 2002;Lowry et al 2004). We investigated this issue in the present study by examining only the 10 continuously variable fruit characters.…”
Section: ] Arbizu Et Al: Studies Of the Daucus Guttatus Complexmentioning
confidence: 99%
“…Sáenz (1981), Pujadas Salvà (2003, Baranski et al (2006), and Mezghani et al (2014) indicated that fruits provided critical taxonomic characters distinguishing taxa within Daucus since fruits tend to show less phenotypic plasticity in comparison with other plant organs. Other studies questioned the utility of fruit characters alone as a practical tool to classify taxa in the Apiales (Downie and KatzDownie 1999;Katz-Downie et al 1999;Spalik et al 2001;Vallejo-Roman et al 2002;Lowry et al 2004). We investigated this issue in the present study by examining only the 10 continuously variable fruit characters.…”
Section: ] Arbizu Et Al: Studies Of the Daucus Guttatus Complexmentioning
confidence: 99%
“…Besides, the diagnostic components of P. gussonei (such as germacrene D) are absent in Lagoecia. Considering the data on chemical composition of the essential oil as well as the molecular and fruit-anatomy characteristics, [33][34][35] the taxonomy of the tribe Lagoecieae might be considered to be reviewed. The tribe of Lagoecieae might be judged as very arti¼cial, in fact Lagoecia is very distant from P. gussonei and the other taxa belonging to the Saniculoideae.…”
Section: Resultsmentioning
confidence: 99%
“…Total DNA was isolated from leaf tissue using NucleoSpin Plant isolation kit (Macherey-Nagel, Düren, Germany) following the manufacturer's instructions. Details of PCR amplifications of ITS1-2 region and sequencing strategies used (including primer locations and characteristics) are provided in Valiejo-Roman et al (2002). PCR products were purified using the DNA cleaning kit from Cytokine (St.-Petersburg, Russia) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%